Optical Investigation of On‐Surface Synthesized Armchair Graphene Nanoribbons. Issue 11 (21st August 2017) - Zhao, Shen; Borin Barin, Gabriela; Rondin, Loïc; Raynaud, Christophe; Fairbrother, Andrew; Dumslaff, Tim; Campidelli, Stéphane; Müllen, Klaus; Narita, Akimitsu; Voisin, Christophe; Ruffieux, Pascal; Fasel, Roman; et al.
Abstract : On‐surface synthesized N = 9‐armchair graphene nanoribbons (AGNRs) are investigated by Raman spectroscopy and AFM/micro photoluminescence measurements. In order to perform the optical experiments, the AGNR film is transferred on a glass substrate through a non‐membrane method. The Raman spectroscopy shows the radial breathing‐like mode characteristic of the 1D nature of GNRs, proving the efficiency of the transfer method. Then, the results of combined AFM/micro photoluminescence measurements are discussed. First, the observation of high‐order Raman lines suggests the 1D nature of the electron–phonon coupling in GNR, similar to the case of carbon nanotubes. Secondly, the origin of the broad luminescence line is discussed in comparison with the predicted gap energy of the 9‐AGNR. Due to its width and energy range, the emission is interpreted as arising from defect sites, missing phenyl rings for instance, that occur during the synthesis of these specific armchair nanoribbons. Abstract : Zhao et al. report on the optical properties of on‐surface synthesized N = 9‐armchair graphene nanoribbons (AGNRs). After being synthesized on Au(111), the AGNR film is transferred on a glass substrate through a non‐membrane method. The radial breathing‐like mode and high‐order Raman lines are observed and related to the one‐dimensional nature of the GNRs. Finally, the origin of a broad luminescence line observed from the GNR film is discussed.